Validating and applying a multidimensional scale to measure public security police stressors in China - Jue Deng; Jianping Ma; Yuanhua Ou; Xianghui Lai; Zhenqiang Li; Xiaoli Zhu (Frontiers in Public Health, 2026)
Background Policing is a highly stressful occupation, with considerable implications for officers' mental health and wellbeing. Despite increasing research on police stress, there remains a critical need for culturally relevant and up-to-date measurement tools, particularly in Eastern countries like China. This study aimed to develop and validate a revised version of the Police Stress Scale (PSS)—the Revised Chinese Public Security Police Stressors Scale (CPSPSS-R)—a tool assessing stressors affecting Chinese public security police officers. Methods The CPSPSS-R was developed using qualitative interviews with 30 police officers and a subsequent psychometric evaluation involving 1,194 in-service officers. The final scale comprised 37 items across four dimensions: excessive workload, lack of skill, organizational issues, and work–family conflict. Results The CPSPSS-R demonstrated excellent reliability and validity, with confirmatory factor analysis supporting the four-factor structure (χ 2 /df = 3.76, TLI = 0.916, CFI = 0.922, SRMR = 0.048, RMSEA = 0.070). The scale also found significant correlations between stressors and demographic variables, including age, gender, rank, and educational level. Conclusions These findings highlight the demand for differentiated, subgroup-specific stress interventions for police officers. As a psychometrically sound and culturally appropriate scale for evaluating stressors experienced by Chinese public security police officers, the CPSPSS-R yields evidence to enhance police management systems and advance police officers' overall wellbeing. More importantly, this scale establishes a vital assessment framework to detect impairments in police officers' psychological adaptation to occupational strain, supporting the design of precise psychological intervention strategies that maintain their long-term mental well-being under constant work-related stress.